Pervious concrete made with electric furnace slag (FEA): mechanical and hydraulic properties - SANDOVAL,G. F. B. (2019)
Abstract The objective of this work is to make feasible the use of FEA slag instead of the conventional bulk aggregate in the pervious concrete (PC) production, reaching the minimum parameters required by NBR16416/2015 and ACI 522R-10. This substitution would minimize the use of natural aggregates, besides taking advantage of a residue that has no specific destination. In order to reach the objective, three FEAs with different grain sizes were chosen: 6-10 mm (A), 10-20 mm (B) and finally a mixture of the two previous ones (C) in the proportion 30-70 respectively. In order to evaluate its mechanical behavior, tests of compressive strength and flexural tensile tests were carried out, while the evaluation of the hydraulic behavior, porosity and constant head permeability test were performed. The compressive strength varies from 19-31MPa and 3-4MPa for flexural tensile strength was obtained. In hydraulic terms, the porosity varied from 15-20% and the permeability coefficient was 10-12mm/s. There is also a direct influence of grains of size less than 4.8 mm (small aggregate) on the compressive strength and permeability of PCs. At the end of the results, it was possible to establish a correlation between the compressive strength, the permeability and the percentage of grains inferior to 4.8mm (sand%), being this positive in relation to the studied variables, that is, the mechanical and hydraulics. Therefore, it has been concluded that the total substitution of conventional aggregates by FEA in CoPe manufacturing will comply with the minimum parameters of NBR 16416/2015.